Fuzzy logic-based controller of the bidirectional direct current to direct current converter in microgrid - Younes Boujoudar; Mohamed Azeroual; Lahcen Eliysaouy; Fatima Zahra Bassine; Aiman J. Albarakati; Ayman Aljarbouh; Alexey Knyazkov; Hassan El Moussaoui; Tijani Lamhamdi (International Journal of Electrical and Computer Engineering (IJECE), 2023)
Microgrids are small-scale power networks that include renewable energy sources, load, energy storage systems, and energy management systems (EMS). Lithium-ion batteries are the most used battery for energy storage in microgrids due to their advantages over other types of batteries. However, to protect the battery from the explosion and to manage to charge and discharge based on state-of-charge (SoC) value, this type of battery requires the use of an energy management system. The main objective of this paper is to propose an intelligent control strategy for energy management in the microgrid to control the charge and discharge of Li-ion batteries to stabilize the system and reduce the cost of electricity due to the high cost of grid electricity. The proposed technique is based on a fuzzy logic controller (FLC) for voltage control. The FLC is based on the measured voltage of the direct current (DC) bus and the fixed reference voltage to generate buck/boost converter signal control. The proposed technique has been simulated and tested using MATLAB/Simulink software which illustrates the tracking of desired power and DC bus voltage regulation. The simulation results confirm that the proposed systems can diminish the deviations of the system's voltage.